Propriedades de adsorção de água em farinhas mistas de arroz e bagaço de cevada pré-gelatinizadas por extrusão termoplástica - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
We recognize the importance and necessity to support the use of products that can be found in excess in nature and, specially, reuse the sub products of the industry. The objective of this work is to collaborate with the development of this new edible product, researching the properties to absorb the water in function of time for certain temperatures and water activities. Therefore, the adsorption kinetics of water was modelled, adjusting the Peleg model to the experimental values and the adsorption isotherms of water on balance were defined through the experimental data being tested using the models of OSWIN, SMITH and PELEG. Te research was conducted in the Laboratories of the University Unit of Science and Technology at UEG in Anapolis – Goias. The development of this work was executed using the static gravimetric method, in which the water activity was held constant with the use of saline solutions. At the end of the studies, the flour showed to be a type of food with properties of water adsorption satisfactory, which can be an alternative to formulate many others food products.
Keywords: Resíduos; Cevada; Isoterma; Extrusão termoplástica; Hordeum vulgare L.; Oryza sativa L.; Waste; Malt; Isotherm; Thermoplastic extrusion; Hordeum vulgare L.; Oryza sativa L.; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA